Update on infective complications in patients treated with alemtuzumab for multiple sclerosis: review and meta-analysis of real-world and randomized studies. Issue 10 (3rd October 2021) - Buonomo, Antonio Riccardo; Viceconte, Giulio; Zappulo, Emanuela; Maraolo, Alberto Enrico; Russo, Cinzia Valeria; Carotenuto, Antonio; Moccia, Marcello; Gentile, Ivan
ABSTRACT: Objective: We aimed to systematically assess the pooled prevalence of infective complications in randomized controlled trials (RCTs) and real-world studies (RWSs) investigating alemtuzumab treatment in multiple sclerosis (MS), also looking at selected infections and their severity. Methods: We included in the analysis RCTs and RWSs investigating the use of alemtuzumab in MS in which infective complications were reported, as well as case reports of rare infections. We conducted a meta-analysis of proportions and a random effect model meta-regression to investigate heterogeneity. Results: The pooled prevalence of infective complications in alemtuzumab treated MS patients is 24%. The most common reported infections are respiratory tract infections (47%) and the most part of the infections are mild-to-moderate (85%). Severe infections account for 6% of the total estimate. We found first-time-reported cases of invasive aspergillosis, hepatitis E virus infection, EBV hepatitis, and cerebral toxoplasmosis. The prevalence of infections is higher in studies conducted before 2009, and in studies with higher proportion of male participants. Conclusions: Clinicians should be aware that the prevalence of serious infections during alemtuzumab can be higher than expected from RCTs. Peculiar opportunistic infections should be considered when evaluating a patient treated with alemtuzumab who develops signs of infection.